O mercado financeiro e a globalização: uma análise sob a perspectiva da efetividade do direito ao desenvolvimento - Fernandes, Ana Carolina Souza (2014)
The free circulation of goods and services, financial capital and information is the basis of the globalisation. When it comes to the role of Law in such context there is a convergence of understandings regarding the mismatch between the current Law and the reality that the Law intents to regulate. Actions taken by governments towards regulation of the market, especially the financial and the capital markets, are essential factors and also decisive for the stability and development. This thesis shall analyze the origin and evolution of financial globalization, and its effects, mainly after the 2008 crisis. It is also intented to contextualize the market regulation as a mean to the effectiveness of the right to development, through the actions of the necessary State. Since this is a descriptive and exploratory study, shall be based on literature, national and alien, using the deductive method, and excepcionally, the inductive method